Sound Reflection from Overhead Stage Canopies Depending on Ceiling Modification - KAMISIŃSKI, Tadeusz; SZELĄG, Agata; RUBACHA, Jarosław (Archives of Acoustics, 2012)
Reflecting structures placed over the stage in auditoria and concert halls should provide sound reflectionin a way that enhances sound emission from the stage without causing acoustic defects in the interior.Model studies conducted by the authors were used to determine the relative level of sound reflection byreflecting structures as a function of frequency for a number of geometric configurations and materials.Analysis of the results allowed drawing conclusions about the effect of modifications of the ceiling over thereflecting panels on the quality of the sound reflected from them. It was shown that modification of theceiling over the reflecting panels by employing highly sound absorbing materials significantly improvedthe characteristics of the reflected sound. Also, certain configurations of elements located in the spaceunder the ceiling should be avoided, as the experiments indicated the occurrence of adverse acousticeffects.